Book Review of Negotiating a Permeable Curriculum - Ted Kesler (Networks: An Online Journal for Teacher Research, 2016)
Negotiating a Permeable Curriculum was first published in 1993 in the National Council of Teachers of English Concept Paper Series. Now it is reprinted in book form as part of the Garn Press Women Scholars Series. In the book, the extended essay is framed by an introduction by senior editor, Bobbie Kabuto, and an interview by Kabuto with Anne Haas Dyson. The final section of the book is a bibliography of Dyson’s most recent publications.
Keywords: writing pedagogy; early childhood; book review